Perceiving and Reimagining Sources: EFL Students’ Reflections on AI-Mediated Report Writing in an Islamic State University - Basir, Amin; Hidayat, Hendi (Journal of English Teaching and Learning Issues, 2025)
This qualitative descriptive study examines how English as a Foreign Language (EFL) students utilize artificial intelligence (AI) tools to source and integrate online information for academic report writing. The study involved 32 third-semester students who wrote reports on Cirebon wedding traditions, utilizing various online sources and self-selected AI tools, including ChatGPT, Quillbot, and Grammarly. Data were gathered through open-ended questionnaires and semi-structured interviews with eight students. Thematic analysis revealed six key themes: the strategic use of multiple AI tools, source selection based on accessibility and relevance, AI-assisted simplification, the evolution of voice and authorship, ethical awareness, and learning transfer. Students displayed a reflective and critical approach, viewing AI not merely as a shortcut but as a dialogic partner in the writing process. The findings highlight how AI not only enhances textual production but also fosters intercultural understanding within EFL contexts. This study contributes to the discourse on digital literacy by providing a localized perspective on AI usage and calls for pedagogies that promote ethical and strategic authorship in AI-mediated academic writing.